(untitled) (Proceedings of the International Conference on Sustainable Management for Peace and Harmony, 2025)
Small and Medium Enterprises (SMEs) are crucial to Indonesia’s economy. However, many SMEs encounter obstacles in enhancing their performance. This study seeks to examine the influence of knowledge management, Artificial Intelligence (AI), and innovation on the performance of SMEs in Indonesia. Data was gathered from 200 SMEs across diverse industrial sectors using the survey method. PLS-SEM was used to validate data and examine the hypothesized relationships. The results of the study show the effective implementation of KM contributes to increasing operational efficiency and driving innovation, which is important to adapt to market changes. By managing knowledge well, SMEs can improve their competitiveness and performance through the identification and utilization of opportunities. Innovation serves as a link between KM and performance, creating an environment that supports the development of new ideas. Additionally, AI acts as a mediator that accelerates decision-making and improves collaboration among employees. The results of this study show that SMEs need investment in an organized knowledge management system and supporting technology to achieve optimal performance and sustainable growth. These findings will be beneficial for practitioners and researchers in the field of marketing and entrepreneurship.